(untitled) (Web of Teachers: Inderscience Research, 2023)
The article "Aiymkhan Lapyzy: Guardians of Cultural Heritage - History and Significance" is a comprehensive review of the folklore and ethnographic ensemble "Aiymkhan Lapyzy", which originated in the early 20th century. The article discusses the key stages of its formation, evolution and significant events that made this ensemble an integral part of the cultural heritage.